Assessment of water quality in the vicinity of Chini Lake, Malaysia - Abdusalam, Youssif Hussin; Islam, Mir Sujaul; Karim, Md Abdul; Mg, Salah; Mohamad Idris, Ali; Noram Irwan, Ramli (Bangladesh Botanical Society, 2019)
Chini lake water is used as a source of water for domestic, industrial and agriculture. The study was carried out to assess the water quality of the lake and surrounding area. Ten sampling sites were selected representing the open water body in the lake. A total of 14 water quality parameters viz. temperature, EC, TDS, DO, pH, turbidity. BOD, COD, TSS, PO4, SO4, NH4, NO3 and salinity were measured. The lowest WQI value 77 was recorded at site S4, respectively, which were found to be slightly polluted. Considering the NWQS, temperature 30.04ºC, EC 31.42 µS/cm, TDS 19.03 mg/l, NO3 - 0.21 mg/l, SO4 - 0.84 mg/l, PO4- 0.05 mg/l, TSS 12.03 mg/l and salinity 0.03 ppt are categorized under class I, while DO 6.15 mg/l, pH 6.73, turbidity 4.22 NTU, BOD 1.63 mg/l, COD 19.50 mg/l and NH4-N 0.20 mg/l the lake water quality are categorized under class II. Total coliform was 273, 412, 868, 267, 495, 406, 929, 953, 441 and 398 cfu/100 ml at all S1 - S10 sites, respectively. While E. coli was found 13, 7, 13, 5, 7, 5, 6, 106, 10 and 7 cfu/100 ml, respectively at all S1 - S10 sites. The highest number of both total coliform 953 cfu/100ml and E. coli 106 cfu/100ml were observed at site S8. The sources of coliforms and E. coli pollution were wastes from human and animals and domestic effluent, which might be due to lack of improper sanitation systems and effects of land use from surrounding agricultural area.